Influence of genomic variations on glanders serodiagnostic antigens using integrative genomic and transcriptomic approaches - Charron, Philippe; Gao, Ruimin; Chmara, John; Hoover, Emily; Nadin-Davis, Susan; Chauvin, Danielle; Hazelwood, Jennifer; Makondo, Kennedy; Duceppe, Marc-Olivier; Kang, Mingsong (Frontiers in Veterinary Science, 2023)
Glanders is a highly contagious and life-threatening zoonotic disease caused by Burkholderia mallei (B. mallei). Without an effective vaccine or treatment, early diagnosis has been regarded as the most effective method to prevent glanders transmission. Currently, the diagnosis of glanders is heavily reliant on serological tests. However, given that markedly different host immune responses can be elicited by genetically different strains of the same bacterial species, infection by B. mallei, whose genome is unstable and plastic, may result in various immune responses. This variability can make the serodiagnosis of glanders challenging. Therefore, there is a need for a comprehensive understanding and assessment of how B. mallei genomic variations impact the appropriateness of specific target antigens for glanders serodiagnosis. In this study, we investigated how genomic variations in the B. mallei genome affect gene content (gene presence/absence) and expression, with a special focus on antigens used or potentially used in serodiagnosis. In all the genome sequences of B. mallei isolates available in NCBI's RefSeq database (accessed in July 2023) and in-house sequenced samples, extensive small and large variations were observed when compared to the type strain ATCC 23344. Further pan-genome analysis of those complete or chromosome-level genome assemblies revealed differences in gene content ranging from 31 to 715 genes with an average of 334 gene presence-absence variations in each strain. The affected genes included some encoded proteins used as serodiagnostic antigens, which were lost due mainly to structural variations. Additionally, a transcriptomic analysis was performed using the type strain ATCC 23344 and strain Zagreb which has been widely utilized to produce glanders antigens. In total, 388 significant differentially expressed genes were identified between these two strains, including genes related to bacterial pathogenesis and virulence, some of which were associated with genomic variations, particularly structural variations. To our knowledge, this is the first comprehensive study to uncover the impacts of genetic variations of B. mallei on its gene content and expression. These differences would have significant impacts on host innate and